Water hammer investigation of shut-down of high-head hydropower plant at very high Reynolds number flows - Karadžić, Uroš (Strojniški vestnik, 2019)
This paper investigates water hammer phenomena in a refurbished high-head hydropower plant Perućica, Montenegro during shut-down of the entire plant - simultaneous closure of the seven Pelton turbine units. In-situ measuring campaign during a number of steady and unsteady conditions has been performed on the plant's open channel, pressurized and tail race sub-systems with primarily goal to define measures that will enable achievement of the plant's installed capacity. In-house software written in Visual Fortran and based on the method of characteristics (MOC) has been developed. Closure of the Pelton turbine distributors is modelled by the two-speed closing law. Dissipation torques in turbine housing and shaft bearings are considered in calculation of the Pelton turbine unit rotational speed change. Numerical results given for standard quasi-steady and convolution based unsteady friction model are compared with results of measurements at flows with very high initial Reynolds numbers (larger than 10^7). Developed numerical model shows good agreement with the results of site measurements. It is shown that the unsteady friction has a small impact on pressure histories in Perućica HPP.
Keywords: ekstremno visoka Reynoldsova števila; emergency shut-down; high Reynolds number; high-head hydropower plants; hitre zapore; Pelton turbine; Peltonova turbine; visokotlačne hidroelektrarne; vodne turbine; vodni udar; water hammers